Causality between corruption and poverty: An analysis for South American countries - Oliveira da Silva, Denilson; Lopes Ribeiro, Lilian; Tatiwa Ferreira, Roberto; Martins Costa, Edward; Urano de Carvalho Castelar, Pablo (Estudios económicos, 2022)
This work aimed to analyze the causality between corruption and poverty in Brazil and a group of seven other South American countries, from 2002 to 2018, using the methodology applied by Dumitrescu and Hurlin (2012) for heterogeneous panels. The variables for corruption employed are the Corruption Perception Index (CPI) and the Control of Corruption (CC) index and, as measures of poverty, the indexes proposed by Foster, Greer, and Thorbecke (1984), considering the poverty and extreme poverty lines. Results suggest one-directional CC causality for all measures of the poverty line, as well as for the P2 indicator of extreme poverty.